Characteristics Of Cataract Patients Suffering From Diabetes Mellitus - Andi Rezky Maulana; Sri Irmandha Kusumardhanu; Muh. Fadli Hidayat (Jurnal EduHealth, 2024)
The visual system is the various components of the eye that function in the process of vision by reacting to light, obtaining information about their environment and helping to recognize the outside world through a visual perception process called vision. Cataract disease is one of the disorders of the human eye, cataract is a condition where the lens of the eye is cloudy due to lens hydration (addition of fluid), lens protein denaturation or both. A metabolic disorder disease, diabetes mellitus, can occur due to a decrease in the insulin hormone produced in the pancreas. A cohort study by the Beaver Dam Eye Study also found an association between diabetes mellitus and cataract formation in adult patients. This literature review aims to determine the characteristics of cataract patients with diabetes mellitus such as gender, age, length of time suffering from diabetes mellitus, and type of cataract morphology. The method used was a literature review with a Narrative Review design to identify and summarize previously published articles on the characteristics of cataract patients with diabetes mellitus. From the 20 articles summarized, it was found that the characteristics of cataract patients suffering from diabetes mellitus were more common in female gender than male with an age range of 40 to 80 years, and the duration of diabetes mellitus in most cataract patients was ≥ 10 years, and the most common cataract morphology in diabetes mellitus is posterior subcapsular cataract.